2012
DOI: 10.1038/hr.2012.116
|View full text |Cite
|
Sign up to set email alerts
|

Low daily salt intake is correlated with albuminuria in patients with type 2 diabetes

Abstract: Both high and low salt intakes have been reported to be associated with an increased risk of cardiovascular events. The aim of this study was to investigate the relationship between daily salt intake and albuminuria, a marker of diabetic nephropathy and cardiovascular disease, in patients with type 2 diabetes. We classified 270 patients with type 2 diabetes, who were not receiving antihypertensive medication into four groups according to their daily salt intake (o8, 8-10, 10-12 and 412 g per day). We investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
(25 reference statements)
3
13
0
Order By: Relevance
“…Seven studies were population based, 10,12,13,[15][16][17][18] and 2 had been conducted in diabetic patients 14,19 or hypertensive subjects. 11,20 Sodium intake was estimated from spot urine samples in 4 studies, 13,16,17,19 from 24-hour urine collections in 5, 10,11,14,15,20 from a food frequency questionnaire in 1, 18 and from dietary recall in 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven studies were population based, 10,12,13,[15][16][17][18] and 2 had been conducted in diabetic patients 14,19 or hypertensive subjects. 11,20 Sodium intake was estimated from spot urine samples in 4 studies, 13,16,17,19 from 24-hour urine collections in 5, 10,11,14,15,20 from a food frequency questionnaire in 1, 18 and from dietary recall in 1.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 247 full-text papers we read, 36 studies, including 73,482 participants, fulfilled the inclusion criteria and provided enough data to be included in at least one meta-analysis. Of these, 11 were crosssectional studies, [10][11][12][13][14][15][16][17][18][19][20] 5 were longitudinal cohort studies, [21][22][23][24][25] and 20 were intervention trials. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] The weighted means of sodium intake were similar among studies in which consumption was assessed by means of spot urine samples 13,16,17,19 (mean, 156 mmol/d; range, 96-209 mmol/ d) 16,17 and 24-hour urine collections 10,11,14,15,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The World Health Organization (WHO) [5] and Korean Diabetes Association [6] recommend a sodium intake of <2,000 mg/day. However, the benefits of low dietary sodium intake in patients with T2DM are still unclear, while some studies reported that reduced sodium intake resulted in albuminuria [7], cardiovascular diseases, and mortality [8]. …”
mentioning
confidence: 99%
“…For example, high salt intake has been reported to promote renal injury in type 2 diabetics, 7 and Suckling et al conducted a meta-analysis concluding that dietary salt restriction attenuated diabetic kidney disease (both type 1 and type 2). 8 However, others reported that when dietary sodium was below 8 g/d, the odds ratio of developing albuminuria was increased 9 and that a reduction in urinary sodium excretion was associated with increased cardiovascular risk and all-cause mortality in type 2 diabetics. 10 The conflicting reports may result from the observational nature of some of the studies, but still leaves a significant gap in knowledge about the role of dietary sodium in cardiovascular risk in type 2 diabetics that could be addressed in a well-controlled clinical study.…”
Section: See Related Article Pp 1189-1195mentioning
confidence: 99%